DEVELOPMENT OF A PLUG-IN FOR VIZUALIZATION OG STRUCTURAL SCHEMES OF COMPUTERS BASED ON THE TEXTUAL DESCRIPTION OF ALGORITHMS OF HARMONIC TRANSFORMS - Prots’ko, I.; Teslyuk, V. (Radio Electronics, Computer Science, Control, 2024)
Context. In many areas of science and technology, the numerical solution of problems is not enough for the further development of the implementation of the obtained results. Among the existing information visualization approaches, the one that allows you to effectively reveal unstructured actionable ideas, generalize or simplify the analysis of the received data is chosen. The results of visualization of generalized structural diagrams based on the textual description of the algorithm clearly reflect the interaction of its parts, which is important at the system engineering stage of computer design. Objective of the study is the analysis and software implementation of structure visualization using the example of discrete harmonic transformation calculators obtained as a result of the synthesis of an algorithm based on cyclic convolutions with the possibility of extending the structure visualization to other computational algorithms. Method. The generalized scheme of the synthesis of algorithms of fast harmonic transformations in the form of a set of cyclic convolution operations on the combined sequences of input data and the coefficients of the harmonic transformation function with their visualization in the form of a generalized structural diagram of the calculator. The results. The result of the work is a software implementation of the visualization of generalized structural diagrams for the synthesized algorithms of cosine and Hartley transformations, which visually reflect the interaction of the main blocks of the computer. The software implementation of computer structure visualization is made in TypeScript using the Phaser 3 framework. Conclusions. The work considers and analyzes the developed software implementation of visualization of the general structure of the calculator for fast algorithms of discrete harmonic transformations in the domain of real numbers, obtained as a result of the synthesis of the algorithm based on cyclic convolutions. The results of visualization of variants of structural schemes of computers clearly and clearly reflect the interaction of its parts and allow to evaluate one or another variant of the computing algorithm in the design process.